2006
DOI: 10.1002/app.25100
|View full text |Cite
|
Sign up to set email alerts
|

Polyetherols obtained from 6‐aminouracil and oxiranes

Abstract: Reactions of 6-aminouracil with an excess of oxiranes (ethylene oxide and propylene oxide) in dimethylsulfoxide in the presence of triethylamine as a catalyst leads to polyetherols with a 1,3-pyrimidine ring. The products are analyzed using IR and 1 H-NMR spectroscopies. The physical properties and thermal stability of the prepared polyetherols are investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 6 publications
1
23
0
Order By: Relevance
“…The thermal stability of the polyetherols obtained from 6-AU and EC was comparable to the thermal stability of those obtained from 6-AU and EO. 15 Ethylene glycol and polyglycols, included in the products, did not reduce their thermal stability. Initial tests of the foaming of the obtained products showed that these polyetherols could be used as components of polyurethane foams of improved thermal stability.…”
Section: Resultsmentioning
confidence: 93%
“…The thermal stability of the polyetherols obtained from 6-AU and EC was comparable to the thermal stability of those obtained from 6-AU and EO. 15 Ethylene glycol and polyglycols, included in the products, did not reduce their thermal stability. Initial tests of the foaming of the obtained products showed that these polyetherols could be used as components of polyurethane foams of improved thermal stability.…”
Section: Resultsmentioning
confidence: 93%
“…These processes can provide the kinetic models mimicking initial steps of the synthesis of polyetherols from oxiranes and azacyclic substrates containing few imide groups, for example isocyanuric acid [29], barbituric acid [30] or 6-amino-uracyl [31]. These azacyclic substrates are sparingly soluble in organic solvents and therefore their reactivities cannot be studied in this class of solvents.…”
Section: Introductionmentioning
confidence: 99%
“…The TG-curve show that 5% mass loss at temperature 150 ºC, and 50% mass loss at 270 ºC occur. Thermal stability of this polyetherol is similar to thermal stability of product obtained from 6-AU and oxiranes [4] and alkylene carbonates [5,6].…”
Section: Resultsmentioning
confidence: 72%
“…These polyetherols can be obtained in reactions of 6-aminouracil (6-AU) with excess of oxiranes (I) [4] or alkylene carbonates (II) [5,6]. where: R = -H, -CH 3 , 3,0 ≤ x + y + z ≤ 10,4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation